2007
DOI: 10.1183/09031936.00163306
|View full text |Cite
|
Sign up to set email alerts
|

Daily versus weekly azithromycin in cystic fibrosis patients

Abstract: Four randomised, placebo-controlled trials have previously documented the clinical benefits of azithromycin (AZM) in cystic fibrosis (CF) patients. The present study examined whether the beneficial effect of AZM is equivalent when administered daily or weekly.A double-blind, randomised study was carried out in 208 CF patients aged 6-58 yrs who were assigned to AZM either 250 mg daily (n5103) or 1,200 mg weekly (n5105) for 6 months, with assessments at baseline and at 1, 3, 6 and 7 months. Patients were taken f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The possibility that macrolides might modify the neutrophilic inflammatory response in CF was first investigated in the early 2000s. Since then, a number of clinical trials have confirmed their beneficial effects both in adults and children [31][32][33][34][35][36][37]. Recently, in a multicentre, randomised, double-blind, placebo-controlled trial, 260 CF patients, not infected with P. aeruginosa, were randomised in a 1:1 ratio to azithromycin 250 mg or 500 mg (based on body weight) 3 days per week, or placebo, for a period of 24 weeks.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…The possibility that macrolides might modify the neutrophilic inflammatory response in CF was first investigated in the early 2000s. Since then, a number of clinical trials have confirmed their beneficial effects both in adults and children [31][32][33][34][35][36][37]. Recently, in a multicentre, randomised, double-blind, placebo-controlled trial, 260 CF patients, not infected with P. aeruginosa, were randomised in a 1:1 ratio to azithromycin 250 mg or 500 mg (based on body weight) 3 days per week, or placebo, for a period of 24 weeks.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…The mechanism of macrolides effect on CF lung disease is unknown. The possibility that macrolides might modify the neutrophilic inflammatory response in CF was investigated and their beneficial effects have been confirmed in a number of clinical trials both in adults and children [12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…(29,30) In addition, it is essential to bear in mind the possibility that resistance to macrolides and other antibiotics will increase, as well as the clinical impact of colonization with more resistant pathogens. (18)(19)(20) …”
Section: Cystic Fibrosismentioning
confidence: 99%
“…McCormack et al (19) RCT Equivalence was demonstrated between the two groups (daily vs. weekly use) with respect to improvements in pulmonary function. Phaff et al (17) RCT Erythromycin resistance in S. aureus isolates increased, as did clarithromycin resistance in H. influenzae isolates.…”
Section: Rctmentioning
confidence: 99%
See 1 more Smart Citation